The representation of the history through de documentary format: the case of "Nostradamus Effect" - López García, Tania (Historia y Comunicación Social, 2014)
The television series Nostradamus Effect, shows many different theories about how would be the end of the world. It emphasized the year 2012 following the knowledge of several cultures as Mayans, Hopis, Christianity and Islamic fundamentalism, it tries to reflect on pictures the surmises that will lead us to the end of our days.
Keywords: Nostradamus Effect; the end of the world; Nostradamus; forecasts